Exploring the Drivers of Workforce Productivity: A Case Study Approach - Karimi, Hengameh; Khawaja, Sarwar (Journal of Ecohumanism, 2025)
This study investigates the critical factors affecting employee productivity within a UK-based construction company, aiming to address overlooked elements in prior research, specifically regarding salary expectations. By administering questionnaires to both direct and midlevel employees, this study identifies key productivity drivers and examines managerial and organisational gaps impacting project outcomes. Key findings reveal that truck availability, worker motivation, rework, tools, and machinery significantly influence productivity levels, aligning with similar studies in the UK and the US. Notably, this research fills a gap by highlighting salary expectations as a primary factor affecting employee turnover, a consideration absents in past studies. The study’s conclusions offer insights applicable to international construction projects, promoting cross-context learning and strategic improvements in workforce management.